Battery diaphragm and preparation method thereof, secondary battery, electric equipment and energy storage system

By inserting bonded particles into the composite coating of the battery separator and attaching the first heat-resistant particles, the problems of insufficient heat resistance performance of the existing battery separator and blockage of the electrolyte channel are solved, and higher heat resistance and circulation stability of the battery separator are achieved.

CN119725993APending Publication Date: 2025-03-28HUAWEI TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311283866.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing battery separators lack heat resistance, resulting in low battery safety performance, and the swelling of bonded resin particles will block the electrolyte channel, resulting in a degradation of battery circulation performance.

Method used

A composite coating structure is adopted, including a heat-resistant base layer and bonded particles embedded in the heat-resistant base layer. The first heat-resistant particles are attached to the surface of the exposed portion of the bonded particles to improve the heat resistance of the bonded particles and the unobstructed properties of the electrolyte channel.

Benefits of technology

It improves the heat resistance and structural stability of the battery separator, extends the cycle life of the battery, and improves the thermal safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725993A_ABST
    Figure CN119725993A_ABST
Patent Text Reader

Abstract

The invention provides a battery diaphragm and a preparation method thereof, a secondary battery, electric equipment and an energy storage system. The composite coating of the battery diaphragm has good heat resistance, a smooth electrolyte passage can be constructed and kept in the cycle process of a battery, and the composite coating can be formed at a time, and is simple to prepare and high in production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a battery separator and a preparation method thereof, a secondary battery, an electrical device and an energy storage system. Background Art

[0002] As one of the main components of secondary batteries, the diaphragm has the functions of a safety medium and regulating the interface between the positive and negative electrodes. The properties of the diaphragm will significantly affect the safety performance and cycle performance of the battery. Most existing commercial diaphragms are polyolefin diaphragms, which have poor heat resistance and will affect the safety performance of the battery. For this reason, the industry often coats inorganic particles on the surface of the polyolefin diaphragm substrate to form a heat-resistant layer, and in order to ensure the fit between the electrode plate and the diaphragm and the transmission of active ions, an adhesive layer is also provided on the surface of the heat-resistant layer. However, the heat-resistant layer and the adhesive layer must be formed in steps, which will significantly increase the process and cost of diaphragm production.

[0003] In order to shorten the preparation process, some literature reports directly mixing heat-resistant inorganic particles with adhesive resin particles so that the adhesive resin particles are dispersed in the heat-resistant layer composed of inorganic particles and protrude relative to the heat-resistant layer. However, when the above-mentioned diaphragm is applied to the battery, the adhesive resin particles will be swollen by the electrolyte, and after swelling, they will become the breaking bridge point of the electrolyte transmission in the diaphragm, causing the battery capacity to drop in the later stage of the cycle. Summary of the invention

[0004] In view of this, the embodiments of the present application provide a battery separator, a secondary battery, an electrical device and an energy storage system. The composite coating of the battery separator has good heat resistance and can construct and maintain a smooth electrolyte path during the battery cycle. The composite coating can be formed in one step, is simple to prepare, and has high production efficiency.

[0005] In a first aspect, the present application provides a battery separator, comprising a substrate and a composite coating disposed on at least one surface of the substrate;

[0006] The composite coating comprises a heat-resistant base layer and a plurality of bonding particles embedded in the heat-resistant base layer; the bonding particles comprise an exposed portion relative to the heat-resistant base layer, and a plurality of first heat-resistant particles are dispersed on a partial surface of the exposed portion;

[0007] The heat-resistant base layer includes a plurality of second heat-resistant particles, and the first heat-resistant particles and all or part of the second heat-resistant particles are made of the same material.

[0008] When the above-mentioned battery separator is applied to the battery, the exposed part of the bonding particles that is not covered by the first heat-resistant particles can be in direct contact with the electrode plate, bonding the battery separator and the electrode plate to improve the structural stability of the final battery; more importantly, the first heat-resistant particles attached to the surface of the exposed part of the bonding particles can act as "isolation points" when the bonding particles swell to prevent the bonding particles from completely blocking the electrolyte channel after swelling, and a "liquid guide channel" can be formed between the first heat-resistant particles to drain the electrolyte from the edge of the separator or the electrode plate to the middle of the electrode plate, which can improve the electrolyte infiltration effect on the electrode plate during the long cycle process, thereby improving the long cycle stability of the battery. The first heat-resistant particles attached to the exposed part can also improve the heat resistance of the bonding particles, thereby improving the heat resistance of the battery separator, so the safety performance of the battery can be further improved.

[0009] In addition, the material of the first heat-resistant particles and all or part of the second heat-resistant particles is the same, and in the preparation process of the composite coating, it can be achieved that "there is no need to first modify the first heat-resistant particles on the surface of the bonding particles", that is, the composite coating can be formed in one step, saving process and further reducing the production cost of the diaphragm.

[0010] In some embodiments of the present application, on any of the bonding particles, along the thickness direction of the battery separator, the orthographic projection area of ​​the plurality of first heat-resistant particles on the bonding particle is 5%-95% of the orthographic projection area of ​​the bonding particle on the heat-resistant base layer. In this way, when the battery separator is applied to a battery, it can ensure that the interfacial bonding force between the battery separator and the electrode plate is high, and that the drainage effect of the electrolyte is better, and it is also beneficial to improve the heat resistance of the bonding particles.

[0011] In some embodiments of the present application, the ratio of the particle size of the first heat-resistant particles to the particle size of the bonding particles is in the range of 1: (6-100). In this way, when the battery separator is applied to a secondary battery, the bonding performance between the battery separator and the electrode plate, as well as the construction of the drainage channel of the electrolyte in the battery can be better considered.

[0012] In some embodiments of the present application, the second heat-resistant particles are selected from at least one of heat-resistant polymer particles or heat-resistant inorganic particles. The above materials have good heat resistance and are easy to obtain.

[0013] In some embodiments of the present application, the particle size of the heat-resistant inorganic particles is in the range of 10 nm-2 μm. This is beneficial to the preparation of the battery separator and ensures that the battery separator has good heat resistance.

[0014] In some embodiments of the present application, the glass transition temperature of the heat-resistant polymer particles is ≥150° C. This is beneficial to further improve the dimensional stability of the battery separator when heated.

[0015] In some embodiments of the present application, the particle size of the heat-resistant polymer particles is in the range of 10 nm to 200 nm. The heat-resistant polymer particles with the above particle size are easy to prepare, and controlling the particle size within the above range is beneficial to the preparation of battery separators.

[0016] In some embodiments of the present application, the first heat-resistant particles and all the second heat-resistant particles are made of the same material, and the sum of the mass of the first heat-resistant particles and the second heat-resistant particles accounts for 80%-99% of the total mass of the composite coating. In this way, the heat resistance of the battery separator and its adhesion to the electrode plate can be taken into account.

[0017] In some embodiments of the present application, the first heat-resistant particles are selected from the heat-resistant inorganic particles, and the second heat-resistant particles are selected from the heat-resistant polymer particles and the heat-resistant inorganic particles. In this way, the battery separator can more easily achieve a lower shrinkage rate and a higher electrolyte infiltration rate.

[0018] In some embodiments of the present application, the mass proportion of the heat-resistant inorganic particles in the composite coating is greater than 50%, and the mass proportion of the heat-resistant polymer particles in the composite coating is less than 10%. Controlling the mass proportions of the heat-resistant inorganic particles and the heat-resistant polymer particles within the above range is conducive to balancing the number ratio of the heat-resistant inorganic particles and the heat-resistant polymer particles, thereby ensuring that the heat resistance of the battery separator is good, and is also conducive to the construction of the electrolyte drainage channel at the interface between the battery separator and the electrode plate, thereby facilitating the cycle performance and thermal safety performance of the battery.

[0019] In some embodiments of the present application, the particle size of the bonding particles is in the range of 1 μm-10 μm. This is conducive to the bonding particles forming an effective exposed portion in the battery separator, which can better adhere the battery separator and the electrode plate together, thereby facilitating the improvement of the final battery cycle performance.

[0020] In some embodiments of the present application, the size of the exposed portion in the height direction of the battery separator is 0.1 μm-7 μm. This is conducive to the bonding of the battery separator and the electrode plate, and can also reserve a buffer space for the expansion of the electrode plate that may occur during the battery cycle, and reserve an exhaust channel for the gas production that may occur during the battery formation process.

[0021] In some embodiments of the present application, the glass transition temperature of the bonding particles is ≤100° C. By controlling the glass transition temperature of the bonding particles to be relatively low, the battery separator and the electrode plate can be fixed under relatively mild conditions, which facilitates the preparation of the battery.

[0022] In some embodiments of the present application, along the thickness direction of the battery separator, the sum of the areas of the orthographic projections of the bonding particles on the heat-resistant base layer accounts for 2%-50% of the area of ​​the heat-resistant base layer. The composite coating contains sufficient bonding particles to ensure strong interfacial bonding between the battery separator and the electrode plate, and can reserve more space for the free flow of electrolyte; at the same time, it can ensure that the heat resistance of the battery separator is good, so the cycle performance and thermal safety performance of the battery can be improved simultaneously.

[0023] In some embodiments of the present application, the mass proportion of the plurality of bonding particles in the composite coating is 1%-20%. In this way, both the bonding performance and the heat resistance of the battery separator can be taken into account.

[0024] In some embodiments of the present application, the composite coating further includes a second binder, and the mass proportion of the second binder in the composite coating is 0.5%-10%. This is beneficial to the molding of the battery separator and can also ensure that the comprehensive performance of the battery separator is good.

[0025] A second aspect of the present application provides a method for preparing the aforementioned battery separator, comprising:

[0026] The bonding particle suspension emulsion and the heat-resistant particle dispersion are mixed to obtain a composite coating slurry;

[0027] The composite coating slurry is coated on at least one surface of the substrate and dried to obtain the battery separator.

[0028] The preparation method has simple process and high production efficiency and can realize large-scale industrial production.

[0029] The third aspect of the embodiment of the present application provides a secondary battery, including a positive electrode sheet, a negative electrode sheet, and a battery separator provided by the second aspect of the embodiment of the present application located between the positive electrode sheet and the negative electrode sheet. Due to the use of the battery separator provided by the embodiment of the present application, the secondary battery has good thermal safety performance and good cycle performance.

[0030] In some embodiments of the present application, the secondary battery is a liquid battery using a liquid electrolyte.

[0031] In some embodiments of the present application, the secondary battery may be any one of a lithium secondary battery, a sodium secondary battery or an aluminum secondary battery.

[0032] The fourth aspect of the embodiment of the present application provides an electric device, including the secondary battery provided by the third aspect of the embodiment of the present application. Since the secondary battery is used for power supply, the electric device has strong market competitiveness.

[0033] In some embodiments of the present application, the above-mentioned electrical equipment includes but is not limited to 3C electronic products, such as mobile phones, laptops, tablet computers, drones, wearable electronic devices, etc. The electrical equipment may also include power vehicles, such as new energy vehicles, electric bicycles, etc.

[0034] The fifth aspect of the embodiment of the present application provides an energy storage system, including the secondary battery provided by the third aspect of the embodiment of the present application. Due to the use of the secondary battery provided by the third aspect of the embodiment of the present application, the energy storage system can have a higher energy density.

[0035] In some embodiments of the present application, the energy storage system includes an electrically connected energy storage device and a power converter, the energy storage device includes a housing cavity and the secondary battery accommodated in the housing cavity, the power converter is used to perform power conversion processing on the voltage and / or current, and input the changed voltage and / or current to the energy storage device, so that the energy storage device can meet the power requirements of the electrical equipment.

[0036] In some implementations of the present application, the energy storage system includes any one of an energy storage power station, a household energy storage system, or a data center energy storage system. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A schematic structural diagram of a cross section of a battery separator provided in one embodiment of the present application;

[0038] Figure 2 A scanning electron microscope (SEM) photograph of the surface of the battery separator provided in Example 2 of the present application;

[0039] Figure 3 This is a SEM photograph of the battery separator of Comparative Example 1.

[0040] Explanation of the accompanying drawings: 100 - battery separator; 10 - substrate; 20 - composite coating; 21 - heat-resistant base layer; 22 - bonding particles; 23 - first heat-resistant particles; 211 - second heat-resistant particles. DETAILED DESCRIPTION

[0041] The separator in a secondary battery, especially a secondary battery using an electrolyte, is generally a thin film with a microporous structure. The battery separator is a key inner layer component with great technical barriers in the battery industry chain. It is generally arranged between the positive electrode plate and the negative electrode plate. Its main function is to separate the positive electrode active material from the negative electrode active material to prevent the contact between the two from causing a battery short circuit; and during the battery cycle, the separator needs to maintain the necessary electrolyte to form an active ion channel to maintain the battery cycle. At present, polyolefin separators are widely used in batteries because of their excellent mechanical strength, good chemical stability, low density and low cost. Common polyolefin separators include polyethylene separators, polypropylene separators or polyethylene / polypropylene composite separators. However, the high temperature resistance of the above separators is a shortcoming. If the temperature continues to rise during the battery cycle, the micropores in the polyolefin separator will shrink, leading to safety accidents such as battery short circuits.

[0042] In order to improve the high temperature resistance of polyolefin separators and simplify the separator production process, the industry has tried to mix adhesive resin particles in the heat-resistant coating and make them protrude from the heat-resistant coating so that the heat-resistant coating itself can achieve heat resistance and adhesive properties. During the hot pressing process of battery preparation, the adhesive particles soften and adhere to the surface of the electrode plate, thereby fixing the battery separator and the electrode plate. However, in the later stage of the battery cycle, the electrolyte needs to flow from the edge of the electrode plate to the middle to ensure that the entire area of ​​the electrode plate is infiltrated by the electrolyte; however, under the long-term infiltration of the electrolyte, the above-mentioned adhesive resin particles will swell, forming a "high wall" to block the movement of the electrolyte in the mixed coating, resulting in inconsistent properties in the local area of ​​the separator, resulting in insufficient electrolyte in the electrode plate to form a broken bridge, thereby generating a black spot dead zone, and it will gradually expand with the increase in the number of battery cycles, eventually causing the battery cycle performance to "dive" and even cause the battery to be scrapped. In addition, it is understandable that the thermal stability of the adhesive resin particles is far inferior to the heat-resistant substances in the heat-resistant coating (for example, ceramic particles, etc.). The part of the adhesive resin particles protruding from the heat-resistant coating is also likely to become the heat-resistant shortcoming of the mixed coating, which is not conducive to the thermal safety performance of the battery.

[0043] In order to solve the above technical problems, the first aspect of the embodiment of the present application provides a battery separator 100, see Figure 1 , the battery separator 100 includes a substrate and a composite coating disposed on at least one side of the substrate;

[0044] The composite coating includes a heat-resistant base layer 21 and a plurality of bonding particles 22 embedded in the heat-resistant base layer 21; the bonding particles 22 include an exposed portion relative to the heat-resistant base layer 21, and a plurality of first heat-resistant particles 23 are attached to a portion of the surface of the exposed portion; it can be understood that the particle size of the first heat-resistant particles 23 is smaller than the particle size of the bonding particles 22. It should be noted that in the embodiment of the present application, the portion of the bonding particles 22 embedded in the heat-resistant base layer 21 can be in direct contact with the substrate 10, or there can be second heat-resistant particles 211 between the bonding particles 22 and the substrate. Figure 1 The positional relationship between the intermediate bonding particles 22 and the substrate 10 is merely an exemplary illustration and does not constitute a limitation on the positional relationship between the two.

[0045] The heat-resistant base layer 21 includes the second heat-resistant particles 211, and the first heat-resistant particles 23 are made of the same material as all or part of the second heat-resistant particles 211. In the embodiment of the present application, the first heat-resistant particles 23 are made of the same material as all or part of the second heat-resistant particles 211, which can also be understood as follows: the composite coating includes heat-resistant particles and bonding particles 22, a part of the heat-resistant particles are distributed on the surface of the exposed part of the bonding particles 22, and are called "first heat-resistant particles 23"; the other part of the heat-resistant particles are distributed in the heat-resistant base layer 21, and are called "second heat-resistant particles 211".

[0046] In the battery separator 100 provided in the embodiment of the present application, the bonding particles 22 embedded in the heat-resistant base layer 21 include an exposed portion exposed relative to the heat-resistant base layer 21, and an embedded portion embedded in the heat-resistant coating layer; the first heat-resistant particles 23 are arranged on a part of the surface of the exposed portion, that is, the surface of the exposed portion of the bonding particles 22 has a portion not covered by the first heat-resistant particles 23, and has a certain bonding effect; when it is applied to a battery, the exposed portion of the bonding particles 22 not attached to the first heat-resistant particles 23 can bond the battery separator 100 and the battery. The first heat-resistant particles 23 attached to the surface of the exposed portion of the bonding particles 22 can serve as "isolation points" to prevent the bonding particles 22 from completely blocking the electrolyte channel after swelling, and a "liquid-conducting channel" can be formed between the first heat-resistant particles 23 to drain the electrolyte from the edge of the battery separator 100 or the electrode plate to the middle of the electrode plate, which can improve the infiltration effect of the electrolyte on the electrode plate during the long cycle, thereby improving the long cycle stability of the battery. The first heat-resistant particles 23 attached to the exposed portion can also improve the heat resistance of the bonding particles 22, thereby improving the heat resistance of the battery separator 100, and thus further improving the safety performance of the battery.

[0047] In addition, the material selection of the first heat-resistant particles 23 and all or part of the second heat-resistant particles 211 is the same, and in the preparation process of the composite coating 20, it can be achieved that "there is no need to first modify the first heat-resistant particles on the surface of the bonding particles", that is, the composite coating 20 can be formed in one step, saving process and further reducing the production cost of the diaphragm.

[0048] In the embodiment of the present application, the composite coating 20 may be formed on a single surface of the battery separator 100 , or may be formed on both opposite sides of the battery separator 100 .

[0049] In some embodiments of the present application, along the thickness direction of the battery separator 100, on any bonding particle 22, the sum of the orthographic projection areas of the plurality of first heat-resistant particles 23 on the bonding particle 22 is a, the orthographic projection area of ​​the bonding particle 22 on the heat-resistant base layer 21 is b, and a / b≤95%. In this way, the heat resistance of the battery separator 100 is improved, the battery separator 100 can be kept with a certain degree of adhesion, and a good electrolyte transmission performance can be exerted during the long cycle of the battery.

[0050] In some embodiments of the present application, along the thickness direction of the battery separator 100, on any bonding particle 22, the orthographic projection area of ​​the plurality of first heat-resistant particles 23 on the bonding particle 22 is 5%-95% of the orthographic projection area of ​​the bonding particle 22 on the heat-resistant base layer 21. That is, for any bonding particle 22, the sum of the orthographic projection areas of the plurality of first heat-resistant particles 23 on the bonding particle 22 is a, and the orthographic projection area of ​​the bonding particle 22 on the heat-resistant base layer 21 is b, 5%b≤a≤95%b. In this way, when the battery separator 100 is applied to the battery, it can ensure that the interfacial bonding force between the battery separator 100 and the electrode plate is high, and it can also ensure that it has a better drainage effect on the electrolyte, and it is also beneficial to improve the heat resistance of the bonding particles 22, so that it can be used to provide a battery with better long cycle performance and better safety performance. Specifically, the value of a mentioned above can be but is not limited to 5%b, 8%b, 10%b, 12%b, 15%b, 18%b, 20%b, 25%b, 30%b, 35%b, 40%b, 45%b, 50%b, 55%b, 60%b, 65%b, 70%b, 75%b, 80%b, 82%b, 85%b, 88%b, 90%b, 92%b, 95%b, etc. In an embodiment of the present application, the battery separator 100 is placed in a scanning electron microscope (SEM) for observation, the sample to be observed is pasted on a sample stage, and the side of the battery separator 100 having the composite coating 20 is facing away from the sample stage (if the battery separator 100 has composite coatings 20 on both opposite sides, the composite coating 20 on either side can be facing away from the sample stage, or the composite coating 20 on the other side can be peeled off), a top view of the composite coating 20 is taken (that is, the surface of the battery separator 100), and the ratio of a and b is calculated using particle size testing software.

[0051] In some embodiments of the present application, the second heat-resistant particles 211 are selected from at least one of heat-resistant inorganic particles or heat-resistant polymer particles. At this time, the material selection of the first heat-resistant particles 23 and the second heat-resistant particles 211 in the battery separator includes the following cases: In some embodiments, the second heat-resistant particles 211 are heat-resistant inorganic particles, and the first heat-resistant particles 23 are heat-resistant inorganic particles. In some embodiments, the second heat-resistant particles 211 are heat-resistant polymer particles, and the first heat-resistant particles 23 are heat-resistant polymer particles. In other embodiments, the second heat-resistant particles 211 are selected from heat-resistant inorganic particles and heat-resistant polymer particles, and the first heat-resistant particles 23 are heat-resistant inorganic particles. In some embodiments, the second heat-resistant particles 211 and the first heat-resistant particles 23 are both selected from heat-resistant inorganic particles and heat-resistant organic particles. In some other embodiments, the second heat-resistant particles 211 are selected from heat-resistant inorganic particles and heat-resistant polymer particles, and the first heat-resistant particles 23 are heat-resistant polymer particles.

[0052] In some embodiments of the present application, the first heat-resistant particles 23 are heat-resistant inorganic particles. In this case, the second heat-resistant particles 211 can be heat-resistant inorganic particles, or a mixture of heat-resistant inorganic particles and heat-resistant polymer particles. In this way, the composite coating 20 is easier to prepare, and the battery separator 100 is easier to achieve a lower shrinkage rate and a higher electrolyte infiltration speed.

[0053] In some embodiments of the present application, the first heat-resistant particles 23 and the second heat-resistant particles 211 are both heat-resistant polymer particles. At this time, the shrinkage performance of the battery separator 100 is average, meeting the thermal safety requirements, but the battery separator 100 can achieve a faster electrolyte infiltration speed.

[0054] In some embodiments of the present application, the first heat-resistant particles 23 and the second heat-resistant particles 211 are selected from heat-resistant inorganic particles and heat-resistant polymer particles. In this case, the advantages of heat-resistant inorganic particles and heat-resistant polymer particles can be simultaneously utilized. Those skilled in the art can select according to application needs.

[0055] In some embodiments of the present application, the material of the inorganic heat-resistant particles includes but is not limited to at least one of aluminum oxide, boehmite, silicon dioxide, magnesium hydroxide, barium sulfate or oxide solid electrolytes. The above-mentioned inorganic materials have good heat resistance and good chemical stability. They will not be swollen by the electrolyte and will not affect the electrochemical reaction of the battery. They are also widely available and easy to process. Among them, the above-mentioned oxide solid electrolytes include but are not limited to those selected from NASICON-type electrolytes (LATP lithium aluminum titanium phosphate), garnet-type electrolytes (LLZO lithium lanthanum zirconium oxide), perovskite-type electrolytes (LLTO lithium lanthanum titanium oxide), LiSICON-type electrolytes, for example: Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li7La3Zr2O 12 (LLZO), Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , Li 0.48 La 0.505 TiO3, etc.

[0056] In some embodiments of the present application, the particle size of the heat-resistant inorganic particles is in the range of 10nm-2μm. That is, the particle size of the first heat-resistant particles 23 and the second heat-resistant particles 211 made of inorganic materials is in the range of 10nm-2μm. In this way, it is beneficial to the preparation of the battery separator 100 and also ensures that the heat resistance of the battery separator 100 is good. In some specific embodiments, the particle size of the heat-resistant inorganic particles is in the range of 50nm-1μm. The heat-resistant inorganic particles distributed in the above-mentioned particle size range are easy to prepare, and are also conducive to the simultaneous attachment of the heat-resistant inorganic particles and the heat-resistant polymer particles on the bonding particles 22; and the heat-resistant inorganic particles have different material properties from the bonding particles 22, and their hardness is relatively large. Controlling their particle size within the above-mentioned range makes them easy to disperse, and is also more conducive to their attachment and bonding to the exposed part of the bonding particles 22 and forming a smooth drainage channel in the later stage of the battery cycle, and will not affect the interfacial bonding force of the bonding particles 22; at the same time, the heat-resistant base layer 21 formed by them also has a more suitable porosity, which is more conducive to the infiltration of the electrolyte. Specifically, the particle size of the heat-resistant inorganic particles can be, but is not limited to, 10nm, 20nm, 30nm, 50nm, 80nm, 100nm, 200nm, 300nm, 500nm, 800nm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2.0μm, etc.

[0057] In some embodiments of the present application, the material of the heat-resistant polymer particles includes, but is not limited to, at least one of polyamide, polyimide (PI), polyamide-imide (PAI), polysulfone (PSU), polyketone (PK), polyetherketone, polytetrafluoroethylene (PTFE), polyfuran, modified or unmodified poly(p-phenylene terephthalamide) (PPTA), and modified or unmodified poly(m-phenylene isophthalamide) (PPIA). Among them, modified poly(p-phenylene terephthalamide) includes, but is not limited to, sulfonated poly(p-phenylene terephthalamide); modified poly(m-phenylene isophthalamide) includes, but is not limited to, sulfonated poly(m-phenylene isophthalamide). Specifically, the material of a single heat-resistant polymer particle may include at least one of the above-mentioned multiple heat-resistant polymers, or a plurality of heat-resistant polymer particles may be formed by mixing different heat-resistant polymer particles. The heat-resistant polymer has a relatively high glass transition temperature (abbreviated as Tg), and will not be deformed by heat during the manufacturing process of the battery separator 100 and the battery. The polymer has good chemical stability and heat resistance, and will not swell and deform during the long cycle of the battery.

[0058] In some embodiments of the present application, the glass transition temperature (Tg) of the heat-resistant polymer particles is ≥ 150°C. For example, 150°C-300°C, etc. In this way, not only can the first heat-resistant particles and the second heat-resistant particles be prevented from deforming during the preparation and cycle of the battery to affect the performance of the battery, but it is also beneficial to further improve the dimensional stability of the battery separator 100 when heated, thereby fully reducing the risk of short circuit of the battery under thermal runaway of the battery, that is, fully ensuring the thermal safety performance of the battery. Specifically, the Tg of the heat-resistant polymer particles (that is, the Tg of the first heat-resistant particles 23 and the Tg of the second heat-resistant particles 211) can be, but not limited to, 150°C, 180°C, 200°C, 220°C, 250°C, 255°C, 260°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, etc. The specific glass transition temperature is also related to the material of the heat-resistant polymer particles, and those skilled in the art can select according to actual needs.

[0059] In some embodiments of the present application, the particle size of the heat-resistant polymer particles is in the range of 10nm-200nm. That is, the particle size of the first heat-resistant particles 23 and the second heat-resistant particles 211 made of polymer is in the range of 10nm-200nm. In this way, it is beneficial for them to be fixed on the exposed surface of the bonding particles 22, and it is also beneficial for them to participate in the formation of the heat-resistant base layer 21; and when the battery separator 100 is applied to the battery, when the above-mentioned a / b value is the same, the number of the first heat-resistant particles 23 on the exposed surface is more, and a larger number of small and criss-crossed "guiding channels" can be formed, which is beneficial to the cycle performance of the battery. In addition, the heat-resistant polymer particles of the above-mentioned particle size are easy to prepare. Specifically, the particle size of the heat-resistant polymer particles can be 10nm, 20nm, 30nm, 50nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, etc.

[0060] In the embodiment of the present application, the first heat-resistant particles 23 and the second heat-resistant particles 211 are separated from the battery separator 100, and then a laser particle size analyzer is used to measure the particle sizes of the first heat-resistant particles 23 and the second heat-resistant particles 211. The particle size testing software can also be directly combined to use SEM to test the particle sizes of the first heat-resistant particles 23 and the second heat-resistant particles 211.

[0061] In some embodiments of the present application, when the material of the first heat-resistant particle 23 and all the second heat-resistant particles 211 is the same, for example, when the first heat-resistant particle 23 and the second heat-resistant particle 211 are both heat-resistant inorganic particles, or both are heat-resistant polymer particles, the sum of the masses of the first heat-resistant particle 23 and the second heat-resistant particle 211 accounts for 80%-99% of the total mass of the composite coating. In this way, the composite coating has good heat resistance and will not occupy too much of the bonding particles 22. Therefore, the battery separator 100 can also achieve a higher interfacial bonding force. Specifically, at this time, the sum of the masses of the first heat-resistant particle 23 and the second heat-resistant particle 211 can be 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, 99%, etc. of the total mass of the composite coating.

[0062] In some embodiments of the present application, when the first heat-resistant particles 23 are inorganic heat-resistant particles and the second heat-resistant particles 211 are a mixture of heat-resistant inorganic particles and heat-resistant polymer particles, the mass proportion of the heat-resistant inorganic particles in the composite coating 20 is greater than 50%, for example, 50%-90%; the mass proportion of the heat-resistant polymer particles in the composite coating 20 is less than 10%, for example, 0.5%-10%. Controlling the mass proportions of the heat-resistant inorganic particles and the heat-resistant polymer particles within the above range is conducive to balancing the effects of the heat-resistant inorganic particles and the heat-resistant polymer particles, thereby ensuring that the heat resistance of the battery separator 100 is good, and is also conducive to the construction of the electrolyte drainage channel at the interface between the battery separator 100 and the electrode plate, thereby facilitating the cycle performance and thermal safety performance of the battery. Specifically, at this time, the mass proportion of the heat-resistant inorganic particles in the composite coating 20 can be 55%, 60%, 65%, 70%, 75%, 80%, 82%, 85%, 88%, 89%, etc., and the mass proportion of the heat-resistant polymer particles in the composite coating can be 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc.

[0063] In some embodiments of the present application, the material of the bonding particles 22 is selected from modified or unmodified acrylic polymers, specifically, it can be but not limited to at least one of polymethyl methacrylate (PMMA), acrylic copolymers, etc. When the bonding particles 22 include multiple different acrylic polymers at the same time, a single bonding particle 22 itself can be composed of multiple different acrylic polymers, or multiple bonding particles 22 can be mixed with different acrylic polymer bonding particles 22. The above substances have good bonding force, and when the battery separator 100 is applied to the battery, it can improve the interfacial bonding force between the battery separator 100 and the electrode plate; at the same time, the above substances can show good elasticity at the formation and operating temperature of the battery, can adapt to the expansion that may occur in the battery during the cycle, and further improve the structural stability of the battery during the cycle.

[0064] In some embodiments of the present application, the glass transition temperature (Tg) of the bonding particles 22 is ≤100°C. Controlling the Tg of the bonding particles 22 within the above range is beneficial to the bonding of the battery separator 100 and the electrode plate, and is beneficial to the preparation of the battery. In some specific embodiments, the Tg of the bonding particles 22 is in the range of (-30)°C to 100°C. In this way, it is beneficial to the high temperature cycle performance of the battery. Specifically, the Tg of the bonding particles 22 can be, but is not limited to, -30°C, -25°C, -20°C, -15°C, -10°C, -5°C, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc.

[0065] In some embodiments of the present application, the composite coating 20 further includes a second binder, and the mass proportion of the second binder in the composite coating 20 is 0.5%-10%. Specifically, the mass proportion of the second binder in the composite coating 20 can be, but is not limited to, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, etc. In some specific embodiments, the second binder is dispersed in the heat-resistant base layer 21, which is used to bond the second heat-resistant particles 211, which is conducive to the molding of the heat-resistant base layer 21 and can improve the structural stability of the heat-resistant base layer 21 during the battery cycle process and when the battery is heated. Among them, the second binder can select any known binder in the art. Specifically, the second binder includes, but is not limited to, polyvinyl alcohol, polyacrylic acid, styrene-butadiene rubber, polyurethane, polyimide-type polymers, etc., which have good bonding force and will not affect the performance of the battery.

[0066] In some embodiments of the present application, the composite coating 20 also includes a thickener. In some specific embodiments, the mass proportion of the thickener in the composite coating 20 is 0.5%-3%. It can be understood that in some embodiments, the composite coating 20 is prepared by coating the composite coating slurry on the substrate 10 and drying it. The application of the thickener can improve the process capability of the composite coating slurry, thereby facilitating the preparation of the battery separator, and the thickener will also remain in the battery separator 100 after drying. Specifically, the mass proportion of the thickener in the composite coating 20 can be, but is not limited to, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, etc. In some embodiments of the present application, the thickener includes, but is not limited to, sodium carboxymethyl cellulose (CMC) and the like.

[0067] In some specific embodiments of the present application, the composite coating 20 also includes a dispersant and a wetting agent, which can promote the dispersion of the first heat-resistant particles 23, the second heat-resistant particles 211 and the bonding particles 22 during the preparation process of the composite coating 20, thereby improving the product yield and production efficiency of the battery separator 100. Among them, the dispersant can be selected from any known dispersant for the heat-resistant coating of the battery separator 100, for example, at least one of polycarboxylate ammonium salts or non-ionic surfactants; the wetting agent can also be selected from any known wetting agent for the heat-resistant coating of the battery separator 100, for example, at least one of siloxane substances, fatty alcohol ether substances, and polyoxyethylene substances. In the composite coating 20, the sum of the mass proportions of the dispersant and the wetting agent is ≤2%, for example, 0.2%-2%.

[0068] It can be understood that in some specific embodiments of the present application, the heat-resistant base layer 21 includes second heat-resistant particles 211, a second binder, a thickener, a dispersant and a wetting agent.

[0069] In some embodiments of the present application, the particle size of the bonding particles 22 is in the range of 1 μm-10 μm. In this way, the bonding particles 22 are evenly dispersed in the heat-resistant base layer 21, thereby improving the uniformity of the battery separator 100, and it is easy to form an exposed portion on the surface of the heat-resistant base layer 21, thereby improving the cycle performance of the battery. In some specific embodiments, the particle size of the bonding particles 22 is in the range of 3 μm-8 μm. Controlling the particle size of the bonding particles 22 within the above range is more conducive to the dispersion and embedding of the bonding particles 22 in the heat-resistant base layer 21, and the height of the exposed part of the bonding particles 22 and the size embedded in the heat-resistant base layer 21 can be controlled within a more appropriate range. The exposed part has a suitable height, which is conducive to the bonding of the battery separator 100 and the electrode plate, and can reserve a buffer space for the expansion of the electrode plate during the battery cycle. In addition, it can also reserve an exhaust channel for gas production during the battery formation process; the part embedded in the heat-resistant base layer 21 has a suitable size, which can enable the bonding particles 22 to be stable in the heat-resistant base layer 21 for a long time during the battery cycle, improve the peeling strength between the battery separator 100 and the electrode plate, and help improve the overall performance of the battery. Specifically, the particle size of the bonding particles 22 can be, but is not limited to, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc.

[0070] In some embodiments of the present application, along the height direction of the battery separator 100, the size of the exposed portion of the bonding particle 22 is 0.1μm-7μm. The bonding particle 22 has a certain elasticity. Controlling the height of its exposed portion within the above range is conducive to the bonding of the battery separator 100 and the electrode pole piece, and can also make a certain gap between the dense heat-resistant base layer 21 and the electrode pole piece. During the preparation of the battery, when the electrolyte is poured into the battery cell, it is conducive to the rapid infiltration of the electrolyte into the electrode pole piece and the battery separator 100; at the same time, it is conducive to the rapid discharge of the gas generated in the electrode pole piece during the battery formation process, which is conducive to the structural stability of the battery. In addition, as before, buffer space can be reserved for the expansion of the battery during the cycle, and the volume energy density of the battery can be taken into account. It is also worth noting that when the bonding particles 22 meet the above parameters, the surface uniformity of the battery separator 100 can be improved. Specifically, the size of the exposed portion of the bonding particles 22 may be, but is not limited to, 0.1 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, etc.

[0071] In the embodiment of the present application, SEM can be used to characterize the height of the exposed portion of the bonding particles 22. Specifically, the battery separator 100 is brittle-broken, freeze-cut or cut to expose the cross section of the composite coating 20, and a cross-sectional photo of the composite coating 20 is taken in the SEM, and the size of the exposed portion of the bonding particles 22 is measured in combination with the particle size test software; wherein, the cross section of the composite coating 20 refers to the exposed cross section after the battery separator 100 is cut by any plane parallel to the thickness direction of the battery separator 100.

[0072] In some embodiments of the present application, the thickness of the heat-resistant base layer 21 is 0.1 μm-6 μm. In some specific embodiments, the thickness of the heat-resistant base layer 21 is 2 μm-4 μm. In the embodiments of the present application, the thickness of the heat-resistant base layer 21 refers to: the maximum size of the heat-resistant base layer 21 along the thickness direction of the battery separator 100 (it should be noted that when measuring the size of the heat-resistant base layer 21 in the thickness direction of the battery separator 100, the bonding particles 22 are not included). Controlling the thickness of the heat-resistant base layer 21 within the above range can make the battery separator 100 have better heat resistance without affecting the energy density of the final battery. Specifically, the thickness of the heat-resistant base layer 21 can be, but is not limited to, 0.1 μm, 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, etc.

[0073] In some embodiments of the present application, the ratio of the particle size of the first heat-resistant particles 23 to the bonding particles 22 is within the range of 1: (6-100). Controlling the above ratio can further optimize the structure of the composite coating. The appropriate particle size ratio makes it easy for the first heat-resistant particles 23 to adhere firmly to the surface of the exposed part of the bonding particles 22. In the process of preparing the battery, applying a small pressure can make the material in the bonding particles 22 overflow from between the first heat-resistant particles 23 and contact and fully bond with the electrode plates, and form a good liquid-conducting channel between the battery separator 100 and the electrode plates, which is beneficial to improving the overall performance of the battery and can further reduce the difficulty of preparing the battery. Specifically, the ratio of the particle size of the first heat-resistant particles 23 to the bonding particles 22 can be, but is not limited to, 1: (15-60), 1: (20-60), 1: (15-40), 1: (20-40), 1: (15-50), 1: (20-50), 1: (40-60), 1: (40-50), 1: (50-60), etc.

[0074] In some embodiments of the present application, along the thickness direction of the battery separator 100, the sum of the areas of the orthographic projections of the bonding particles 22 in the composite coating 20 on the heat-resistant base layer 21 accounts for 2%-50% of the area of ​​the heat-resistant base layer 21. The area of ​​the heat-resistant base layer 21 is specifically understood as the orthographic projection area of ​​the heat-resistant base layer 21 on the substrate 10. It can be understood that although the surface of the exposed portion of the bonding particles 22 has the first heat-resistant particles 23 to form a drainage channel for the electrolyte, the appropriate proportion of the bonding particles 22 can avoid the formation of a large number of "high walls". Therefore, the sum of the areas of the bonding particles 22 is controlled within the above range, so that the composite coating 20 has sufficient bonding particles 22 to ensure that the interface bonding force between the battery separator 100 and the electrode plate is strong, and more space can be reserved for the free flow of the electrolyte; at the same time, the heat resistance of the battery separator 100 can be guaranteed to be good, so the cycle performance and thermal safety performance of the battery can be improved simultaneously. Specifically, the sum of the areas of the orthographic projections of the bonding particles 22 on the heat-resistant base layer 21 can be 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, etc., of the area of ​​the heat-resistant base layer 21.

[0075] In some embodiments of the present application, the mass proportion of the bonding particles 22 in the composite coating 20 is 1%-20%. In some specific embodiments, the mass proportion of the bonding particles 22 in the composite coating 20 is 5%-15%. In this way, the bonding performance and heat resistance of the battery separator 100 can be taken into account. Specifically, the mass proportion of the bonding particles 22 in the composite coating 20 can be 1%, 2%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 18%, etc.

[0076] In the embodiment of the present application, the substrate 10 is selected from the substrate commonly used in the battery separator 100. Specifically, the substrate 10 is a porous polyolefin separator, including but not limited to a porous polyethylene separator, a porous polypropylene separator, and the like.

[0077] In some embodiments of the present application, the porosity of the substrate 10 is 30%-50%. Appropriate porosity enables the substrate 10 to have good mechanical strength and electrolyte retention capacity. Specifically, the porosity of the substrate 10 can be 30%, 35%, 40%, 45%, 50%, etc.

[0078] Accordingly, the embodiment of the present application also provides a method for preparing a battery separator 100, comprising:

[0079] S01, mixing the bonding particle suspension emulsion and the heat-resistant particle dispersion to obtain a composite coating slurry;

[0080] S02, coating the composite coating slurry on at least one surface of the substrate, and drying to obtain a battery separator 100.

[0081] In the embodiment of the present application, in step S01, the bonding particle suspension is obtained by dispersing the bonding particles in a first medium, and the first medium includes but is not limited to at least one of water, a mixture of water and ethanol, ethylene glycol, glycerol, isopropyl alcohol, propylene glycol, butanol, and acetic acid; the heat-resistant particle dispersion is obtained by dispersing the heat-resistant particles in a second medium, and the second medium includes but is not limited to at least one of water, a mixture of water and ethanol, ethylene glycol, glycerol, isopropyl alcohol, propylene glycol, butanol, and acetic acid. According to the foregoing, the first heat-resistant particles and the second heat-resistant particles in the battery separator are essentially the same, the difference is that the two are distributed in different positions in the composite coating, and there is no need to distinguish their raw materials; therefore, the heat-resistant particles in the composite coating slurry include the raw materials used to form the first heat-resistant particles and the second heat-resistant particles. During the preparation process, the above-mentioned first medium and the second medium can be the same or different, as long as they can be mixed to form a uniform composite coating slurry.

[0082] In step S01, by adjusting the ratio of the bonding particle suspension emulsion and the heat-resistant particle dispersion, part of the heat-resistant particles can adhere to the surface of the bonding particles, and then after coating and drying in step S02, the aforementioned battery separator provided in the embodiment of the present application can be obtained. The above preparation method has simple steps, and simply provides the bonding particle suspension emulsion and the heat-resistant particle dispersion, and then combines with a simple preparation process to form the battery separator provided in the embodiment of the present application in one step, with low production cost and high production efficiency.

[0083] In some embodiments of the present application, step S01 further includes adding a glue containing a second binder to the composite coating slurry. The second binder includes but is not limited to at least one of polyvinyl alcohol, polyacrylic acid, styrene-butadiene rubber, polyurethane, and polyimide-type polymers. The addition of the second binder can significantly reduce the difficulty of forming the heat-resistant base layer and improve the stability of the composite coating. In some specific embodiments, the dispersion of the second binder is 1%-20% of the mass of the composite coating slurry.

[0084] In some embodiments of the present application, in step S01, the above-mentioned second adhesive glue also includes a thickener. The mass proportion of the thickener in the composite coating slurry is 0.5%-3%. In some specific embodiments, the mass proportion of the thickener includes but is not limited to sodium carboxymethyl cellulose (CMC).

[0085] In some specific embodiments of the present application, step S01 further includes adding a dispersant and a wetting agent to the composite coating slurry. The dispersant includes but is not limited to at least one of polycarboxylic acid ammonium salt or non-ionic surfactant; the wetting agent includes but is not limited to at least one of siloxane substances, fatty alcohol ether substances, and polyoxyethylene substances. In some specific embodiments of the present application, in the composite coating slurry, the sum of the mass of the dispersant and the wetting agent in the composite coating slurry accounts for ≤0.2% of the mass.

[0086] In some specific embodiments of the present application, in step S01, the bonding particle suspension, the heat-resistant particle dispersion, the glue, the dispersant, the wetting agent and the dispersion medium (e.g., water) are mixed and stirred sufficiently to obtain a composite coating slurry. With the coordination of the above substances, in the composite coating slurry, an appropriate amount of heat-resistant particles are more likely to adhere to the surface of the bonding particles, making it easier to obtain the battery separator of the embodiment of the present application.

[0087] In some embodiments of the present application, in step S01, the composite coating slurry includes the following components in parts by weight: 20-80 parts of a bonding particle suspension, 20-80 parts of a heat-resistant particle dispersion, 1-20 parts of a glue solution, 0.1-0.5 parts of a dispersant, and 0.1-0.5 parts of a wetting agent. In this way, the battery separator can be obtained more smoothly. In addition, by adjusting the ratio of the composite coating slurry within the above range, the distribution of the heat-resistant inorganic particles and the heat-resistant polymer particles can also be regulated, that is, the first heat-resistant particles in the final battery separator can be adjusted to be heat-resistant inorganic particles, or the second heat-resistant particles can be adjusted to be a mixture of heat-resistant polymer particles and heat-resistant inorganic particles.

[0088] In some specific embodiments of the present application, in step S01, the mass proportion of the bonding particles is 5%-65% based on the total weight of the bonding particle suspension. In this way, it is beneficial to mix it with other components to obtain a uniform composite coating slurry, which is more conducive to the preparation of battery separators. Specifically, based on the total weight of the bonding particle suspension, the mass proportion of the bonding particles can be but is not limited to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, etc.

[0089] In some specific embodiments of the present application, in step S01, the mass proportion of the heat-resistant particles is 1%-20% based on the total weight of the heat-resistant particle dispersion. Similarly, this can not only obtain a more uniform heat-resistant particle dispersion, but also make it easier to mix with other components to obtain a uniform composite coating slurry. Specifically, based on the total weight of the heat-resistant particle dispersion, the mass proportion of the heat-resistant particles can be but is not limited to 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc.

[0090] In some embodiments of the present application, the proportion of the first heat-resistant particles, the proportion of the bonding particles, and the thickness of the heat-resistant base layer in the final composite coating can be adjusted by adjusting the amount of the bonding particle suspension and the amount of the heat-resistant particle dispersion. In other embodiments, the above parameters can also be adjusted by the content of the bonding particles in the bonding particle suspension and the content of the heat-resistant particles in the heat-resistant particle dispersion. In addition, the thickness of the heat-resistant base layer can also be adjusted by the coating process parameters in step S02.

[0091] In some embodiments of the present application, in step S01, the solid content of the composite coating slurry is 5%-50%. Controlling the solid content of the composite coating slurry within the above range is beneficial to its coating and also to regulating the thickness of the composite coating (specifically the thickness of the heat-resistant base layer). Specifically, the solid content of the composite coating slurry can be, but is not limited to, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.

[0092] In some embodiments of the present application, in step S02, the coating includes but is not limited to micro-gravure coating, wire rod coating, hanging coating, spray coating, etc. Those skilled in the art may select according to actual needs.

[0093] In some embodiments of the present application, in step S02, the drying condition is: the substrate coated with the composite coating slurry is placed in an oven and dried at 40° C.-80° C. Specifically, the drying temperature can be, but is not limited to, 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., etc.

[0094] The present application also provides a secondary battery, including a positive electrode sheet, a negative electrode sheet, and a battery separator 100 provided in the present application embodiment located between the positive electrode sheet and the negative electrode sheet. Due to the use of the battery separator provided in the present application embodiment, the secondary battery has good thermal safety performance and good cycle performance.

[0095] In some embodiments of the present application, the secondary battery is a liquid battery using a liquid electrolyte.

[0096] In the embodiment of the present application, the secondary battery may be, but is not limited to, an alkali metal secondary battery such as a lithium secondary battery, a sodium secondary battery, an aluminum secondary battery, etc. The secondary battery may be, but is not limited to, a wound battery or a laminated battery.

[0097] In the embodiments of the present application, the positive electrode sheet may be any positive electrode sheet known in the art, and the negative electrode sheet may be any negative electrode sheet known in the art. Specifically, the positive electrode sheet may include a positive current collector and a positive active material layer disposed on the surface of the positive current collector; in some embodiments, the positive active material layer includes a positive active material and a binder. In some specific embodiments, the positive active material layer also includes a conductive agent.

[0098] The positive electrode current collector includes but is not limited to metal foil or alloy foil. Specifically, when the battery is a lithium secondary battery, the metal foil may be aluminum foil, or carbon-coated aluminum foil. Specifically, when the battery is a sodium secondary battery, the metal foil may be but is not limited to aluminum foil or carbon-coated aluminum foil.

[0099] In the embodiment of the present application, there is no special restriction on the binder and the conductive agent in the positive electrode active material, and it can be any known binder and conductive agent for positive electrode sheets in the field. Exemplarily, the binder includes but is not limited to at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyacrylate, polyacrylamide (PAM), polyimide (PI), etc. The conductive agent may specifically include but is not limited to at least one of acetylene black (AB), Ketjen black, super P conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers, etc.

[0100] The negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector. In some embodiments, the positive electrode active material layer includes a negative electrode active material, a binder, and an optional conductive agent. Specifically, when the battery is a lithium secondary battery, the metal foil may be a copper foil, or a carbon-coated copper foil. Specifically, when the battery is a sodium secondary battery, the metal foil may be, but is not limited to, an aluminum foil or a carbon-coated aluminum foil.

[0101] In the embodiments of the present application, there is no particular limitation on the binder and the conductive agent in the negative electrode active material, and they can be any known binder and conductive agent for negative electrode sheets in the art. For example, the binder includes but is not limited to at least one of styrene butadiene rubber (SBR), etc. The conductive agent can specifically include but is not limited to at least one of acetylene black (AB), Ketjen black, super P conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers, etc.

[0102] In some embodiments of the present application, the preparation of the battery includes:

[0103] S11, stacking or winding the positive electrode sheet, the negative electrode sheet and the battery separator to obtain a bare battery cell; wherein the battery separator is located between the positive electrode sheet and the negative electrode sheet;

[0104] S12, performing the processes of packaging, baking, liquid injection, standing, forming, exhausting, etc. on the bare battery cell to obtain a secondary battery.

[0105] Accordingly, the embodiment of the present application also provides an electric device, including the secondary battery provided in the embodiment of the present application. Since the secondary battery is used for power supply, the electric device has strong market competitiveness.

[0106] In some embodiments of the present application, the above-mentioned electrical equipment includes but is not limited to 3C electronic products, such as mobile phones, laptops, tablet computers, drones, wearable electronic devices, etc. The electrical equipment may also include power vehicles, such as new energy vehicles, electric bicycles, etc.

[0107] The embodiment of the present application also provides an energy storage system, including the secondary battery provided in the embodiment of the present application. Due to the use of the secondary battery provided in the embodiment of the present application, the energy storage system can have a higher energy density.

[0108] In some embodiments of the present application, the energy storage system includes an electrically connected energy storage device and a power converter, the energy storage device includes a housing cavity and the secondary battery accommodated in the housing cavity, the power converter is used to perform power conversion processing on the voltage and / or current, and input the changed voltage and / or current to the energy storage device, so that the energy storage device can meet the power requirements of the electrical equipment.

[0109] In some embodiments of the present application, the energy storage system includes but is not limited to any one of an energy storage power station, a household energy storage system, or a data center energy storage system.

[0110] The technical solution of the present application is further described in detail below with multiple embodiments.

[0111] Example 1

[0112] S01, mixing heat-resistant particle dispersion (specifically boehmite particles with a particle size of 700nm, polyfuran dicarboxamide m-phenylenediamine dispersion with a particle size of 65nm), bonding particle suspension (specifically acrylic polymer particles with a particle size of 5.5μm), a glue containing a second binder (specifically styrene-butadiene rubber (SBR)) and a thickener (specifically sodium methyl cellulose), a dispersant (specifically sodium dodecyl sulfate) and a dispersion medium (specifically water), and after sufficient mixing, a composite coating slurry with a solid content of 43.5% is obtained; wherein, based on the total weight of the composite coating slurry, the mass content of SBR is 5%, the mass content of CMC is 0.5%, and the mass proportion of the dispersant is 0.2%.

[0113] S02, providing a substrate (specifically a polyethylene film with a thickness of 7 μm and a porosity of 40%), evenly coating the composite coating slurry on two opposite sides of the substrate, and drying to obtain a battery separator.

[0114] Example 2-Example 11

[0115] The only difference between Example 2-11 and Example 1 is that Example 2-11 simply adjusts the ratio of the composite coating slurry to obtain the battery separator of Example 2-11. Please refer to Table 1 for the specific parameters of each battery separator.

[0116] Diaphragm performance test

[0117] (1) Morphology test: The battery separators prepared in each embodiment and comparative example were subjected to SEM test. In the field of view with a magnification of 2000 times of SEM, the orthogonal projection area of ​​the first heat-resistant particles on the bonding particles on the surface of the battery separator (denoted as a) and the orthogonal projection area of ​​the bonding particles on the heat-resistant base layer (denoted as b) were calculated, and the arithmetic average of a / b for each embodiment and comparative example was calculated; at the same time, the ratio of the orthogonal projection area of ​​each bonding particle on the heat-resistant base layer to the area of ​​the heat-resistant base layer was determined (denoted as c), and the average value was calculated. The results are summarized in Table 1. Among them, a typical SEM photo of the surface of the battery separator of Example 2 is shown in Table 1. Figure 2 As shown, a typical SEM photo of the surface of the battery separator of Comparative Example 1 is as follows Figure 3 shown.

[0118] (2) Heat resistance test: The battery separators prepared in each embodiment and comparative example were baked at 150°C for 1 hour, and the longitudinal (MD) dimensional shrinkage and transverse (TD) dimensional shrinkage of the battery separators were calculated. Wherein, transverse dimensional shrinkage = (lateral dimension of the battery separator before baking - transverse dimension of the battery separator after baking) / transverse dimension of the battery separator before baking × 100%; longitudinal dimensional shrinkage = (longitudinal dimension of the battery separator before baking - longitudinal dimension of the battery separator after baking) / longitudinal dimension of the battery separator before baking × 100%.

[0119] Preparation of batteries

[0120] ① Preparation of positive electrode sheet: Add positive electrode active material (specifically lithium iron phosphate), conductive agent (specifically super p), and positive electrode binder (specifically polyvinylidene fluoride) into a dispersion medium (specifically N-methylpyrrolidone) at a mass ratio of 96.5:1.0:2.5, stir evenly, and obtain positive electrode slurry;

[0121] The positive electrode slurry is coated on the two opposite surfaces of the positive electrode current collector (specifically aluminum foil) by using a coating device, and the positive electrode sheet is obtained through processes such as drying, cold pressing and welding of the pole ears.

[0122] ② Preparation of negative electrode sheet: Add negative electrode active material (specifically graphite), conductive agent (specifically super p), negative electrode slurry thickener (specifically CMC) and negative electrode binder (specifically SBR) to the dispersion medium (specifically deionized water) at a mass ratio of 96.5:1.0:1.5:1.5, stir evenly to obtain negative electrode slurry;

[0123] The negative electrode slurry is coated on the opposite sides of the negative electrode current collector (specifically copper foil) using a coating device, and the negative electrode sheet is obtained through processes such as drying, cold pressing and welding of the pole ears.

[0124] ③ Preparation of batteries: Wind the above-mentioned positive electrode sheet, negative electrode sheet and battery separator prepared in each embodiment and comparative example to obtain a wound bare battery cell, and place the battery separator between the positive electrode sheet and the negative electrode sheet; package and bake in sequence, then inject electrolyte, form and exhaust to obtain the lithium secondary battery of each embodiment and comparative example. The electrolyte is a 1 mol / L LiPF6 solution, and the electrolyte solvent is ethylene carbonate, propylene carbonate and diethyl carbonate in a volume ratio of 1:1:1.

[0125] Battery performance test

[0126] (1) Interface adhesion test: disassemble the above bare battery cells and test the interface adhesion between the battery separator and the positive electrode sheet and the negative electrode sheet. Specifically, cut the battery separator and the positive electrode sheet into 30 mm wide strips, and then bond one side of the positive electrode sheet to the steel plate with double-sided tape to prepare a bonding sample, and peel the battery separator from the positive electrode sheet in the opposite direction of 180° to form an opening, and use a universal tensile testing machine to peel it from the opening at a rate of 50 mm / min, so that the battery separator and the positive electrode sheet are gradually separated along the length of the bonded surface. The force value when the battery separator and the positive electrode sheet are separated is automatically obtained by the testing machine, and the interface adhesion between the battery separator and the positive electrode sheet is calculated by force value / sample width. The test results are summarized in Table 2.

[0127] (2) Electrolyte wetting rate test: The battery separator was cut into 5 mm wide strips, suspended horizontally and fixed, and then a drop of 10 μL of the aforementioned electrolyte was dripped in the middle. The electrolyte diffusion length was measured after 60 s in mm, which is the wetting rate of the sample.

[0128] (3) Battery cycle performance test: The batteries prepared in each embodiment and comparative example were subjected to a core capacity test at 25°C and 0.2C, and then discharged at a constant current to 2.5V and left to stand for 30 minutes;

[0129] After the battery was placed at 55°C for 4 hours, it was charged at 0.5C constant current and constant voltage to 3.65V / 0.05C cut-off, and after standing for 30 minutes, it was discharged at 0.5C constant current to 2.5V and stood for 30 minutes as one cycle. After 3000 cycles, the capacity retention rate of the battery was recorded.

[0130] The capacity retention rate = the capacity of the battery at 3000 cycles / the capacity at the first cycle × 100%. The test results are recorded in Table 2.

[0131] Table 1

[0132]

[0133] Table 2

[0134]

[0135] It should be noted that when the composite coating slurry contains both heat-resistant inorganic particles (X) and organic heat-resistant particles (Y) (Examples 1-5, 8-13), the heat-resistant base layer also includes X and Y at the same time, and the type of the first heat-resistant particles attached to the exposed portion of the bonding particles needs to refer to the "first heat-resistant particles" column in Table 1. Among them, only X is filled in, indicating that the first heat-resistant particles only include the first heat-resistant particles (Examples 1-5, 9-13); and in Example 8, the first heat-resistant particles include X and Y at the same time.

[0136] Please refer to the parameters in Table 1 and Table 2. The battery separator provided in the embodiments of the present application has a lower MD shrinkage rate and TD shrinkage rate, indicating that it has good heat resistance. At the same time, the interface bonding force between the battery separator and the electrode plate is relatively suitable, which can ensure the structural stability of the battery during a long cycle, and is also conducive to the smooth discharge of the gas generated during the battery formation process; and the electrolyte can infiltrate the battery separator more quickly. It can be inferred from the cycle capacity retention rate data of the batteries in each embodiment that the battery separator provided in the embodiments of the present application has a good liquid retention ability during the long cycle of the battery.

[0137] In the embodiment of the present application, "n1-n2" represents a range value, including endpoint values ​​at both ends. For example, the value of the parameter n can be 0.5-15, which means that the value of the parameter n can be between 0.5 and 15, including the endpoint values ​​0.5 and 15.

[0138] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A battery separator, characterized in that: It comprises a substrate and a composite coating disposed on at least one side of the substrate; The composite coating comprises a heat-resistant base layer and a plurality of bonding particles embedded in the heat-resistant base layer; the bonding particles comprise an exposed portion relative to the heat-resistant base layer, and a plurality of first heat-resistant particles are attached to a portion of the surface of the exposed portion; The heat-resistant base layer includes a plurality of second heat-resistant particles, and the first heat-resistant particles and all or part of the second heat-resistant particles are made of the same material.

2. The battery separator according to claim 1, characterized in that: On any of the bonding particles, along the thickness direction of the battery separator, the orthographic projection area of ​​the plurality of the first heat-resistant particles on the bonding particle is 5% to 95% of the orthographic projection area of ​​the bonding particle on the heat-resistant base layer.

3. The battery separator according to claim 1 or 2, characterized in that: The ratio of the particle sizes of the first heat-resistant particles to the bonding particles is in the range of 1:(6-100).

4. The battery separator according to any one of claims 1 to 3, characterized in that: The second heat-resistant particles are selected from at least one of heat-resistant polymer particles and heat-resistant inorganic particles.

5. The battery separator according to claim 4, characterized in that: The particle size of the heat-resistant inorganic particles is in the range of 10 nm to 2 μm.

6. The battery separator according to claim 4 or 5, characterized in that: The glass transition temperature of the heat-resistant polymer particles is ≥150°C.

7. The battery separator according to any one of claims 4 to 6, characterized in that: The particle size of the heat-resistant polymer particles is in the range of 10 nm to 200 nm.

8. The battery separator according to any one of claims 1 to 7, characterized in that: The first heat-resistant particles and all the second heat-resistant particles are made of the same material, and the sum of the masses of the first heat-resistant particles and the second heat-resistant particles accounts for 80%-99% of the total mass of the composite coating.

9. The battery separator according to any one of claims 4 to 7, characterized in that: The first heat-resistant particles are selected from the heat-resistant inorganic particles, and the second heat-resistant particles are selected from the heat-resistant polymer particles and the heat-resistant inorganic particles.

10. The battery separator according to claim 9, characterized in that: The mass proportion of the heat-resistant inorganic particles in the composite coating is greater than 50%, and the mass proportion of the heat-resistant polymer particles in the composite coating is less than 10%.

11. The battery separator according to any one of claims 1 to 10, characterized in that: The particle size of the bonding particles is in the range of 1 μm to 10 μm.

12. The battery separator according to any one of claims 1 to 11, characterized in that: In the height direction of the battery separator, the size of the exposed portion is 0.1 μm-7 μm.

13. The battery separator according to any one of claims 1 to 12, characterized in that: The glass transition temperature of the bonding particles is ≤100°C.

14. The battery separator according to any one of claims 1 to 13, characterized in that: Along the thickness direction of the battery separator, the sum of the areas of the orthographic projections of the bonding particles on the heat-resistant base layer accounts for 2% to 50% of the area of ​​the heat-resistant base layer.

15. The battery separator according to any one of claims 1 to 14, characterized in that: The mass proportion of the plurality of bonding particles in the composite coating is 1%-20%.

16. The battery separator according to any one of claims 1 to 15, characterized in that: The composite coating further includes a second binder, and the mass proportion of the second binder in the composite coating is 0.5%-10%.

17. A method for preparing a battery separator according to any one of claims 1 to 16, characterized in that: include: The bonding particle suspension emulsion and the heat-resistant particle dispersion are mixed to obtain a composite coating slurry; The composite coating slurry is coated on at least one surface of the substrate and dried to obtain the battery separator.

18. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet and a battery separator as claimed in any one of claims 1 to 16, wherein the battery separator is arranged between the positive electrode sheet and the negative electrode sheet.

19. An electrical equipment, characterized in that: The electric device comprises the secondary battery as claimed in claim 18.

20. An energy storage system, characterized in that: The energy storage system comprises the secondary battery as claimed in claim 18.